Is preoperative ultrasound tumor size a prognostic factor in endometrial carcinoma patients? - Ambrosio, Marco; Raffone, Antonio; Alletto, Andrea; Cini, Chiara; Filipponi, Francesco; Neola, Daniele; Fabbri, Matilde; Arena, Alessandro; Raimondo, Diego; Salucci, Paolo; Guerrini, Manuela; Travaglino, Antonio; et al. (Frontiers in Oncology, 2022)
Objective: We aimed to assess the prognostic value of preoperative ultrasound tumor size in EC through a single center, observational, retrospective, cohort study. Methods: Medical records and electronic clinical databases were searched for all consecutive patients with EC, preoperative ultrasound scans available to ad hoc estimate tumor size, and a follow-up of at least 2-year, at our Institution from January 2010 to June 2018. Patients were divided into two groups based on different dimensional cut-offs for the maximum tumor diameter: 2, 3 and 4 cm. Differences in overall survival (OS), disease specific survival (DSS) and progression-free survival (PFS) were assessed among the groups by using the Kaplan–Meier estimator and the log-rank test. Results: 108 patients were included in the study. OS, DSS and PFS did not significantly differ between the groups based on the different tumor diameter cut-offs. No significant differences were found among the groups sub-stratified by age, BMI, FIGO stage, FIGO grade, lymphovascular space invasion status, myometrial invasion, lymph nodal involvement, histotype, and adjuvant treatment. Conclusions: Preoperative ultrasound tumor size does not appear as a prognostic factor in EC women.